Anatomical feasibility study of the infraspinatus muscle neurotization by lower subscapular nerve - Krajcová, Aneta; Makel, Michal; Ullas, Gautham; Němcová, Veronika; Kaiser, Radek (Neurological research, 2023)
OBJECTIVES: To investigate the anatomical feasibility of the infraspinatus branch of the suprascapular nerve (IB-SSN) reconstruction by lower subscapular nerve (LSN) transfer. METHODS: The morphological study was performed on 18 adult human cadavers. The length of the distal stump of the IB-SSN, the length of the LSN available for reconstruction and diameter of both stumps were measured. The feasibility study of the LSN to IB-SSN transfer was performed. RESULTS: The mean length of the IB-SSN to the end of its first branch was 40.9 mm (±4.6). Its mean diameter was 2.3 mm (±0.3). The mean length of the LSN stump, which was mobilized from its original course and transferred to reach the distal stump of the IB-SSN was 66.5 mm (±11.8). Its mean diameter was 2.1 mm (±0.3). The mean ratio between LSN and IB-SSN diameters was 0.9 (±0.1). The nerve transfer was feasible in 17 out of 18 cases (94.4%). CONCLUSION: This study demonstrates that direct LSN to IB-SSN transfer is anatomically feasible in most cases in the adult population. It may be used in cases of complex scapular fractures resulting in severe suprascapular nerve injury.
Keywords: plexus brachialis; Humans; Brachial Plexus; scapular fracture; studie proveditelnosti; dospělí; nervový transfer; lower subscapular nerve; lidé; Nerve Regeneration; regenerace nervu; Rotator Cuff; rotátorová manžeta; Adult; Suprascapular nerve; nerve transfer; Feasibility Studies; brachial plexus injury; Nerve Transfer